Ultrastructure of hyphal cells of Trichophyton tonsurans - Amaliya Stepanova; Sybren de Hoog; Nataliya Vasilyeva; Konstantin Raznatovskiy; Galina Chilina (Mazandaran University of Medical Sciences, 2020)
Background and Purpose: Trichophyton tonsurans is a widely distributed anthropophilic dermatophyte causing different diseases of skin. In the literature limited data are available about the morphogenesis of vegetative mycelium of T. tonsurans and related anthropophilic dermatophytes. The aim of present study was to describe ultrastructural patterns of development, cellular organellography and septal pore apparatus structure of in vitro growing vegetative mycelium of T. tonsurans. Materials and Methods: Trichophyton tonsurans strain RCPFF 214/898 was grown on solid Czapek's Agar (CzA) at 28ºС. For investigation of colonies morphology we used methods of light-, scanning and transmission electron microscopy (SEM and TEM). Results: Differences in morphogenesis of aerial and substrate hyphae were revealed. Mitochondrial reticulum and fibrosinous bodies were shown in T. tonsurans for the first time. The septal pore apparatus in hyphal cells of was comprised Woronin bodies and septal pore plugs. Woronin bodies (0.18 μm), located with 1‒4 near the pore, were spherical, membrane-bound, and had a homogeneous, electron-dense content. The cells of aerial and submerged hyphal cells of T. tonsurans contain two nuclei. Conclusion: Mature cells of substrate hyphae appeared more active than comparable cells in the aerial mycelium. During the maturation process, the differences in number and morphology of mitochondria, number of vacuoles, and in the synthesis of different types of storage substances were revealed. Presence of "mitochondrial reticulum" and variable types of storage substances in submerged hyphal cells suggested higher levels of metabolic activity compared to aerial mycelium.